2020
DOI: 10.12688/hrbopenres.13017.1
|View full text |Cite
|
Sign up to set email alerts
|

Rare Disease Research Partnership (RAinDRoP): a collaborative approach to identify the top 15 research priorities for rare diseases

Abstract: Background: The Rare Disease Research Partnership (RAinDRoP) was established in 2018 to bring together a wide variety of diverse voices in the rare disease community in Ireland and form a research partnership. This approach enabled clinicians, patients, carers and researchers to work together to identify top research priorities for rare diseases, which focused on a life-course perspective rather than a disease-specific need.                                                                                       … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…In this study, patients, family members, and researchers from several disease areas participated in a cross-disease study, and it became apparent that the difficulties faced by patients with rare diseases were often common regardless of the specific of the diseases being represented. Our results are supportive of the existing literature on the feasibility of priority setting targeted on multiple diseases [ 47 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, patients, family members, and researchers from several disease areas participated in a cross-disease study, and it became apparent that the difficulties faced by patients with rare diseases were often common regardless of the specific of the diseases being represented. Our results are supportive of the existing literature on the feasibility of priority setting targeted on multiple diseases [ 47 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the seven research topics listed under the topic title ‘particularly important research topics for strengthening future research on rare diseases’—‘impediments to daily life’, ‘financial burden’, ‘concerns about working and schooling’, ‘anxiety’, ‘pessimism’, ‘mental state specific to genetic diseases’, and ‘burden of hospital visits’—point to desirable research topics that can improve understanding and help create strategies for resolving or reducing burden. Regarding these high-priority research topics, ‘financial burden’ and topics related to psychological issues are also in line with the results of studies reported in the existing literature [ 12 , 47 ]. However, to the best of our knowledge, the presentation of the following topics as high priorities for research attention is something unique in our research results: ‘impediments to daily life’, ‘concern about working and schooling’, and ‘the burden of hospital visits’.…”
Section: Discussionsupporting
confidence: 81%
“…These were in the areas of pulmonary fibrosis ( 40 ), musculoskeletal diseases ( 8 ), liver glycogen storage disease ( 39 ), cystic fibrosis ( 37 ), idiopathic intracranial hypertension ( 36 ), and dystrophic epidermolysis bullosa ( 35 ). One study ( 38 ) was concerned with priority-setting across multiple rare diseases. Two studies were concerned with ultra-rare conditions with a prevalence under 1 in 50,000 ( 35 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings also suggest that eliciting priorities from patients witd related rare diseases may be a useful strategy through which to ensure that greater numbers of patients are involved. This is particularly useful in settings where logistical barriers to participation or the small size of rare disease populations in a particular setting may be obstacles to conducting priority-setting focused around a single rare disease ( 38 ). However, the participation of patients from multiple rare diseases may shift attention away from disease-specific issues and toward identifying shared, system-level and quality-of-life-related issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation